FEATURES OF THE ALPHA ACTIVITY OF THE BRAIN ON THE BACKGROUND OF MEDITATIVEPSYCHOLOGICAL TRAINING - A. S. Yanina (Бюллетень сибирской медицины, 2016)
The aim of the study was to identify the characteristics of the alpha activity of the brain on the background of meditative psychological training, depending on experience and qualifications.Materials and methods. Examined 30 volunteers of 25-45 years old, 12 men and 18 women. Depending on the experience of meditative practices, the participants were divided into three groups: a group with no experience of meditation (beginners), group practicing Kundalini yoga in General classes (1-3 times a week) – average level, and a group of professionals (yoga teachers, practicing for at least three years and having a daily practice). All participants did not had neurological and psychiatric diseases, and had no dependence on alcohol or drugs and was relatively healthy. A study was conducted of the electrical activity of the brain at rest, during and after the meditative psychological training. As a result we acquired data for the frontal, Central, occipital and temporal leads.Results. Identified a number of changes of EEG parameters in the application of meditation techniques, which depended on the experience and qualifications of the subjects. Changes of alpha activity occur in all areas of the brain with the development of meditation techniques, whereas newcomers have changes mainly in the frontal region. The index of alpha-rhythm at rest is higher in groups with experience of meditation practice. The given material allows to recommend psychological training (meditation techniques of Kundalini yoga) to reduce the level of fatigue and correction of psycho-emotional excitation.